A highly efficient single‐phase sine‐wave inverter with single‐switch high‐frequency modulation. Issue 6 (18th July 2017) - Faizal Abdullah, M.; Iqbal, Shahid; Ishak, Dahaman
Abstract : This paper presents a highly efficient single‐phase sine‐wave inverter with single‐switch high‐frequency modulation. In this topology, a control circuit is connected at the lower arm of a full‐bridge inverter to control the output voltage across the full‐bridge inverter. The switch at the lower arm of the full‐bridge inverter controls the output voltage of the full‐bridge inverter by increasing or reducing the voltage level at the lower arm of the inverter. This switch of lower arm is controlled by a high‐frequency sinusoidal pulse width modulation (SPWM) switching signal, while the power switches of the full‐bridge inverter operate with a square‐wave switching signal at the line frequency to unfold DC–AC inversion, thus producing a sinusoidal voltage at the load. Both computer simulation and experiment are carried out to verify the performance of the proposed topology. Experimental results from a 1000‐W laboratory prototype are presented to testify and validate the analysis, design, and performance of the proposed topology. The results show that the proposed topology has nearly sinusoidal output voltage and current waveforms with a total harmonics distortion of less than 5%. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.